Varicose vein surgery versus foam sclereotherapy to prevent extension of venous reflux with time - Fatih Islamoglu (Annals of Circulation - Peertechz Publications, 2020)
In the treatment of Chronic Venous Insufficiency (CVI) High Ligation (HL) and stripping of the saphenous varicose veins, and percutaneous phlebectomy have been the main options for many years. Modern management of CVI includes treatment of the cause (reflux) and result (varicose veins). Reflux should be treated before varicosities because if the cause is not eliminated, the varicose veins will recur [1].